CONSISTENCY OF JUSTICE IN RELIGION DEFENDING WOMEN'S RIGHTS - Syaiful Annas (Universitas Islam Negeri (UIN) Mataram, 2019)
In a responsive legal framework, insistence on legal change is a natural thing, because the law should be seen as a rule that is closely linked to social reality. The existence of changing social realities, usually followed by a sense of justice that changes society and the law should also change. The reality of community life, especially relations between men and women, has changed from time to time. This is influenced by many things, including economic development, technology, education, and law.